Legal Protection of Children's Rights in Early Marriage - Nurjannah; Al Munawar, Said Agil Husin; Aslati (Universitas Medan Area, 2025)
This article aims to find out the age of readiness to marry in early marriage in the review of Islamic law and Indonesian Positive Law against early marriage and legal protection of children's rights in early marriage. The problem is focused on how the readiness age of marriage in early marriage based on Islamic law and positive law, how legal protection of children's rights in early marriage. The theoretical references used are the theory of legal protection and the theory of benefit in Islamic law. Data were collected through literature study and analyzed qualitatively. This study concludes that the readiness of marriage age in Islamic Law can be carried out by prospective brides who have not or have reached puberty if they have fulfilled the conditions and pillars of marriage by paying attention to the benefits. Based on the Compilation of Islamic Law, the minimum age of marriage for men is 19 years and for women is 16 years. Based on Positive Law Marriage Law No. 16 of 2019 in Article 7 Paragraph (1) marriage is permitted if the man and woman reach the age of 19 years. If in certain circumstances married under the age of 19 years can apply for Dispensation to the Court with urgent reasons and supporting evidence. In early marriage, legal protection of children's rights includes age limits, marriage dispensation and protection of children's rights including protection of education and awareness, supervision and protection from violence, physical and mental readiness, agreement and consent in early marriage. With this protection, the rights of children in early marriage can be protected.